Highly Accurate Water Level Measurement System Using a Microcontroller and an Ultrasonic Sensor. Issue 4 (May 2019) - Mohammed, Saleem Latteef; Al-Naji, Ali; Farjo, Mashael M.; Chahl, Javaan
Abstract: In many conditions, the conventional liquid data monitoring based on an ultrasonic sensor provides the unreliable readings due to the dynamically changed water level. In addition, in some conditions, it needs not only measuring water level but also needs to measure the volume and control water surplus or deficiency. To solve these issues, this paper proposes an accurate non-contact water measurement system based on a microcontroller and an ultrasonic sensor to measure the level and volume of liquids in small tanks without any contact. The proposed system also provides automatically controlling the water level with an alarm system to provide early warning of water surplus or deficiency. Microcontroller PIC16F877A is used to drive the sensor circuit and measure the time change of the reflected echoes from the water surface received by the ultrasonic (PING) sensor that correspond to the changes in the water level. The experimental results illustrate the effectiveness of the proposed system to measure the level and volume of water over 30 cm range with small error rates (SSE = 0.033 cm, RMSE = 0.034 cm and MAE = 0.029 cm for level measurement and SSE = 0.025 liter, RMSE = 0.026 liter and MAE = 0.021 liter for volume measurement) and excellent correlation coefficients (SCC = 0.9997 and KCC = 0.9951), thus provide accurate results for continuous measurement of the water level and volume in industrial applications.